The Influence of Power Training on Maluku Inkanas Karate Athletes' Kick Speed Speed - Theophilia Wakole; Albertus Fenanlampir; Johni Melvin Tahapary (Peneliti.net, 2023)
This study aims to determine whether there is an effect of power training on mawashi kick speed in Maluku INKANAS karate athletes. By getting the results of the initial test (pre test) and post test (post test) of the effect of power training on mawashi kick speed in Maluku INKANAS karate athletes. Based on the calculation results, it can be seen that tcount = 7.631 and then consulted with the critical figure for the data ttable at both the 5% and 1% significance level by first determining the db or df where db or df = N-2 = 15-2 = 13. Thus for a significant level of 5% it is known that the value of ttable = 2.160 While for a significant level of 1% it is known that the value of ttable = 3.012 That means that at a significant level of 5% it is smaller than tcount greater than a significant level of 1% or ttable<tcount>ttable or in other words it can be concluded that 2.160 < 7.631 > 3.012. Based on the hypothesis testing criteria, if tcount > ttable, the alternative hypothesis or Ha is accepted and vice versa, the null hypothesis is rejected. Based on the test above, it can be concluded that power training has an effect on the speed of mawashi kicks in Maluku INKANAS karate athletes. That means the alternative hypothesis 〖(H〗_a) is accepted and the null hypothesis is rejected 〖(H〗_o).